ATTITUDINAL FACTORS TO ENCOURAGE LEARNERS’ CAPABILITIES IN LEARNING ENGLISH - Dwi Warry Octaviana (Institut Pendidikan Indonesia Garut, 2018)
Attitudinal factors that relate to second language acquisition will perform one or both of two functions. First, they will be factors that encourage intake. They are simply factors that encourage the learners to communicate with speakers of the target language, and thereby obtain the necessary input, or intake, for language acquisition. Second, attitudinal factors relating to acquisition will enable the learners to utilize the language heard for acquisition. Simply hearing a second language with understanding appears to be necessary but it is not sufficient for acquisition to take place. The learners must not only understand the input but must also, in a sense, be open to it. The following of attitudinal factors that relate posited predictors of second language proficiency to those two functions are integrative motivation and instrumental motivation. The presence of integrative motivation should encourage the learners to interact with speakers of the second language out of sheer interest, and thereby obtain intake. Meanwhile, instrumental motivation will encourage the learners to interact with second language speakers in order to achieve certain ends.